Evidence of Dividend Catering Theory in Malaysia: Implications for Investor Sentiment - Mamunur Rashid; Fauzias Mat Nor; Izani Ibrahim (Contemporary Economics, 2013)
This study investigates the key determinants of corporate performance in Malaysia. Using panel data (2002-2007) of 361 companies listed in Malaysia, the study finds dividend per share, use of debt, number of board members, and last year's performance to be the most significant determinants of corporate performance across four selected industries: trading or services, property, consumer products, and industrial products. This study also finds that dividend per share is influenced by market performance and is followed by last year's dividend and size of the dividend. These findings exhibit the presence of dividend catering incentives. As such, market demand for dividends drives corporate dividends. The study concludes that investor sentiment influences corporate decisions in Malaysia.
Keywords: G02; G12; G32; 330; dividend catering theory; investor sentiment; Malaysia